Is breastfeeding related to bone properties? A longitudinal analysis of associations between breastfeeding duration and pQCT parameters in children and adolescents - Kühn, Tilman (Matern Child Nutr, 2012)
Nutritive and bioactive components of human milk could be involved in programming metabolic systems that affect bone growth throughout the life course. Bone properties in childhood and adolescence might differ, depending on breastfeeding duration. Thus, breastfeeding could be a relevant factor in the context of primary osteoporosis prevention. The prospective association between breastfeeding duration and bone properties was investigated using the data of 284 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study. Breastfeeding duration was assessed during infancy. Bone properties were measured by peripheral quantitative computed tomography (pQCT) at ages 5–23 years. Cortical volumetric bone mineral density, cortical bone mineral content, strength strain index, total cross‐sectional area of the bone and cross‐sectional area of the cortical bone were determined at the 65% site of the radius. Linear regression analyses were performed to check for differences in pQCT parameters of subjects who had not or shortly been breastfed (0–16 weeks) and subjects who had been breastfed for a long duration (≥17 weeks). Multivariable models adjusted for age, gender, forearm length, muscle cross‐sectional area, body mass index standard deviation score (SDS), height SDS and socio‐economic status did not yield associations between breastfeeding duration and pQCT parameters. These findings suggest neither protective nor adverse effects of prolonged breastfeeding on bone health in childhood and adolescence. Influences of early nutrition on bone growth might be overridden by current effects of mechanical loads on bone physiology.